Cytopathology of soft tissue and bone lesions - Khalbuss, Walid E. (Essentials in cytopathology, 2011)
Cytopathology Soft Tissue and Bone Lesions by Walid E. Khalbuss and Anil V. Parwani will fulfill the need for an easy-to-use and authoritative synopsis of soft tissue and bone cytopathology. This volume, part of the Essentials in Cytopathology book series, fits into the lab coat pocket and is ideal for portability and quick reference. Each volume in the series is heavily illustrated with a full color art program, while the text follows a user-friendly outline format. Walid E. Khalbuss, MD, PhD, FIAC is Associate Professor of Pathology at the University of Pittsburgh Medical Center - Shadyside Hospital, Pittsburgh, Pennsylvania. Anil V. Parwani, MD, PhD, is Associate Professor of Pathology at the University of Pittsburgh Medical Center - Shadyside Hospital, Pittsburgh, Pennsylvania. Introduction to soft tissue and bone cytopathology: a practical approach -- Diagnostic accuracy of FNA of soft tissue and bone lesions -- Cytopathology of spindle cell lesions of soft tissue and bone -- Cytopathology of soft tissue and bone lesions containing giant cells -- Cytopathology of soft tissue lesions with predominance of epithelioid, round/polygonal cells, glandular cells, inflammatory cells -- Cytopathology of adipocytic soft tissue tumors -- Utilizing cytology as an adjunct to frozen section to enhance the intraoperative diagnosis of bone and soft tissue tumors -- Ancillary studies in FNAC of soft tissue and bone lesions.